(untitled) (Research, Society and Development, 2024)
Objective: To evaluate the association between prenatal care and the incidence of prematurity, highlighting the importance of quality monitoring during pregnancy. Methodology: A literature review was conducted of scientific publications from June 2019 to June 2024. Initially, 118 studies were identified, of which five were selected based on inclusion criteria. Results and Discussion: The results indicate that prematurity affects approximately 10% of births in Brazil, with associated risk factors such as socioeconomic status and previous preterm births. Frequent prenatal visits are a protective factor. Conclusion: Quality prenatal care is crucial in preventing preterm births, with a direct relationship between the number of visits and the reduction of prematurity.